PD-L1 and p53 expression in squamous cell carcinoma of the oropharynx depending on human papilloma virus status - D. Sh. Polatova; A. Yu. Madaminov; A. V. Savkin; A. I. Nurzhabov; N. K. Asamedinov; D. A. Ibragimova; R. R. Davletov; S. K. Nasirov (Опухоли головы и шеи)
Introduction. High-risk human papilloma virus (Hpv), especially genotype 16, causes oropharyngeal squamous cell carcinoma (OSCC). It is detected in about 70 % of tumors developing from lymphoid tissue of the tonsils or the base of the tongue. Due to the increased number of Hpv-positive OSCC, Hpv status is considered a marker of OSCC clinical outcome. Easy testing, low cost, reliability, and high sensitivity of immunohistochemical analysis for p16INk4a allowed to widely use this method for Hpv status determination.Aim. To determine the association between programmed death-ligand 1 (pD-L1) and p53 expression and presence of indirect Hpv marker – p16INk4a – in patients with OSCC.Materials and methods. The study included 76 patients with OSCC т1–4N0–3m0 who received treatment at the Republican Specialized Scientific and practical medical Center of Oncology and Radiology (n = 37) and its Tashkent branch (n = 39) between 2015 and 2020. for all selected patients, retrospective immunohistochemical analysis for the presence of p16INk4a, pD-L1 and р53 in  tumor  samples  fixed  with  formalin  in  paraffin  blocks  was  performed.  In  our  work,  immunohistochemical  examination for p16INk4a was the only relevant tool for Hpv status determination. To reinforce its prognostic significance, we used additional molecular markers pD-L1 and p53 which play an important role in carcinogenic transformation and OSCC progression.Results. The results of immunohistochemical analysis showed that p16INk4a overexpression was accompanied by positive pD-L1 reaction in 46 % (6/13) of cases; there were no cases of positive expression of mutant type p53. wild type p53 was identified in only 1 (3 %) case in combination with p16INk4a overexpression.Conclusion. The developed panel consisting of 3 molecular markers (p16INk4a, pD-L1 and р53) may open new horizons in accurate prognosis, risk stratification and understanding of OSCC molecular signature. This, in turn, will help clinicians in selection of individual therapy strategies for treatment de-escalation and outcome optimization.